THE INFLUENCE OF GADGETS ON THE SOCIAL BEHAVIOR OF STUDENTS AT MTS TARBIYATUL ISLAMIYAH SOKOPULUHAN PUCAKWANGI PATI - Nurul Hidayah; Rofiq Faudy Akbar (SocioEdu: Sociological Education, 2024)
This research aims to investigate the intensity of gadget usage, the social behavior of students, and the influence of gadgets on the social behavior of students at MTs Tarbiyatul Islamiyah. The method employed is quantitative, with a non-experimental approach and the use of simple random sampling technique. The sample size consists of 75 respondents, and data collection is conducted through questionnaires. The results of this indicate that the data on gadget usage intensity yield percentages of 42% for respondents answering "always & often," 31% answering "sometimes," and 27% answering "never." Meanwhile, their social behavior obtains percentages of 55% for respondents answering "never," 26% answering "sometimes," and 19% answering "always & often." The obtained data testing result shows that the t-value is greater than the t-table (5.370 > 0.1914), where Ha is accepted and Ho is rejected. The coefficient of determination is 28.3%. Therefore, it can be concluded that the intensity of gadget usage at MTs Tarbiyatul Islamiyah is categorized as moderate, indicating that students can use these devices without difficulty. Regarding their social behavior at school, it depicts that they are not overly dependent on gadgets due to various factors preventing reliance on these devices. The influence of gadgets on the social behavior of students at MTs Tarbiyatul Islamiyah obtains a significance value of 28.3%, indicating a positive impact.